Contextualizing Bronze Age Obsidian Use at the 'Ritual Spring' of Mitza Pidighi (Sardinia). Issue 2 (21st December 2015) - Freund, Kyle P.
Abstract: This study focuses on obsidian consumption at the 'ritual spring' of Mitza Pidighi in west-central Sardinia, Italy. The site dates to the late Nuragic I to Nuragic III phases of the Bronze Age (ca. 1350–850 B.C.) and is found just east of a contemporaneous residential village, Nuraghe Pidighi. While recent years have seen a surge of archaeological literature on the subject of obsidian use at residential sites throughout the island, there has been little consideration of its role in other archaeological contexts, a research bias that this presentation aims in part to redress. For this study, 142 obsidian artifacts from Mitza Pidighi were analyzed non-destructively using a Thermo Scientific ARL Quant'X EDXRF spectrometer to determine their geological origins. In addition, each artifact was analyzed techno-typologically to allow for the reconstruction of the entire chain of events leading up to an artifact's discard. The sourcing results show that obsidians from all four Sardinian subsources are represented at the site, although most come from just one outcrop; the typological analysis indicates that people were physically knapping obsidian near the well to create expedient flake tools and non-prismatic bladelets. In combination, these results have important implications for interpreting the social, economic, and symbolic function of Mitza Pidighi and in understanding the role of obsidian outside of domestic contexts.